A Study on the Access of Ministry, Government Agencies, and Law Enforcement Authority to Electronic System Organizers' Data and Systems - Ajisatria Suleiman (Center for Indonesian Policy Studies (CIPS), 2021)
Access to data and systems of Electronic System Organizers (ESOs) is a sensitive issue because it is considered a means of coercion (dwang middelen) that might infringe personal data protection, freedom of speech, individual privacy that also related to intellectual property rights and trade secrets. In light of this, further in-depth analysis is needed to assess whether The Indonesian Ministry of Communication and Informatics (MOCI) Regulation No. 5/2020 on Electronic System Organizers (ESOs) has accommodated various key elements to safeguard the general principles of human rights, intellectual property rights, and personal data protection. This paper concludes that access to ESO's system might not be the best practice and should be taken as a last resort after all mitigation actions on information security have been carried out.
Keywords: 330; Data; Data Governance; Electronic System Organizers; ESO; Personal Data Protection; Data Protection; Freedom of Speech; Privacy; Individual Privacy; Social Media; MOCI; Ministry of Communication and Informatics; Permenkominfo Regulation No. 5/2020; MOCI Regulation No. 5/2020; Electronic System Organizers; Human Rights; Intellectual Property Rights; Data Privacy Rights